Prey detection in carabid beetles (Coleoptera: Carabidae) in woodland ecosystems by PCR analysis of gut contents - Lucija ŠERIĆ JELASKA; Damjan FRANJEVIĆ; Sven D. JELASKA; William O.C. SYMONDSON (European Journal of Entomology, 2014)
Predatory carabid beetles are important for regulating prey abundance in terrestrial ecosystems. While surveys of carabid diet have revealed many insights into trophic interactions, the high species diversity and heterogeneous developmental stages of prey identified in the gut have made further advances difficult. In addition, the carabid gut contains partially digested and mainly soft tissue parts of the prey species, difficult to identify by traditional methods. Molecular gut content analysis (MGCA) avoids these disadvantages but to date has been limited primarily to revealing pest species in agricultural fields. Here we used MGCA to screen for the presence of Lepidoptera in carabid guts, in woodland ecosystems, in both Croatia and the UK. Data on carabids positive for Lepidoptera were compared with those from previous work on the same carabid assemblages, screened for earthworms, slugs, woodlice and springtails. In both locations, the prey group most frequently detected was earthworms, followed by slugs and Lepidoptera and then finally by woodlice and springtails. The composition of the diet changed with season, carabid sex, and carabid size. In both locations, Lepidoptera were the third most frequent prey, with 27% of carabids testing positive in Croatia and 20% in UK, suggesting that carabids could be significant predators of Lepidoptera in woodland ecosystems and may potentially play an important role in controlling moth pests.